Comparative Evaluation of Structural Systems for Tapered Tall Buildings - Kyoung Sun Moon (Buildings, 2018)
Structural efficiency of tapered tall buildings has been well recognized, and many tall buildings of tapered forms have been built throughout the world. Tall buildings are built with an enormous amount of building materials. As one of the most efficient structural forms for tall buildings, the contribution of tapered forms to saving structural materials coming from our limited natural resources could be significant. Structural design of tall buildings is generally governed by lateral stiffness rather than strength. This paper systematically studies the structural efficiency of tapered tall buildings in terms of lateral stiffness. Tall buildings of various heights and angles of taper are designed with different structural systems prevalently used for today’s tall buildings, such as diagrids, braced tubes, and core-outrigger systems. The heights of the studied buildings range from 60 to 100 stories, and the corresponding height-to-width aspect ratios in their non-tapered prismatic forms range from 6.5 to 10.8. The angles of taper studied are 1, 2, and 3 degrees. Gross floor area of each building of the same story height is maintained to be the same regardless of the different angles of taper. Based on design studies, comparative evaluation of the various structural systems for tapered tall buildings is presented.